Fare l’America or Learn to Live in it? Italian Immigration in Peru - Mario Pera (Diasporas: Circulations, Migrations, Histoire)
This article analyzes the influence of the Italian colony who immigrated to Peru from the colonial era to the mid-twentieth century. It deals with the mutual influence observed in the social, economic and political fields through various institutions and companies that Italian immigrants or their descendants founded, and which allowed the transmission of numerous cultural aspects between the two nations.